The flows and balances of P, K, Ca and Mg on intensively managed Boreal high input grass and low input grass-clover pastures - Järvenranta, Kirsi; Virkajärvi, Perttu; Heinonen-Tanski, Helvi (Agricultural and Food Science, 2014)
The main objective of the study was to compare nutrient balances of phosphorus (P), potassium (K), magnesium (Mg) and calcium (Ca) on fertilized grass pasture (high input) and unfertilized grass-clover pasture (low input) both grazed by dairy cattle. The second aim was to quantify P loss in surface runoff from the fertilized grass pasture. The study was conducted on a lysimeter field that included two surface runoff collector ditches. The whole area was rotationally stocked five times per year and the amount of milk was recorded. Nutrient balances were negative on both grass and grass-clover pastures except the P balance for grass pasture, which was 18 kg ha-1 positive. The amount of total P in the surface runoff from fertilized grass pasture was 1.2–0.9 kg ha-1 y-1. It seems that in short-term ley farming, grass-clover swards can retain nutrients in the soil better than pure grass swards.